Nitreto de carbono grafítico associado a nanopartículas plasmônicas de prata e cobre - Queiroz, Emanuel Pereira de (2022)
The present work aims to elucidate the structural, optical and photocatalytic properties of gC3N4 and derivated nanocomposites from the addition of Ag and Cu nanoparticles, in different proportions. The g-C3N4 material was synthesized from thermopolimerization of urea. The concentration of the nanoparticles, in mono- or bi-metallic form was 10% w.t. in relation of g-C3N4. The synthesized nanocomposites was g-C3N4/Ag, g-C3N4/Cu, gC3N4/Ag2Cu, g-C3N4/AgCu, g-C3N4/AgCu2. To elucidate the structural characteristics were used the XRD, XPS and FTIR techniques; for the study of the optical properties, were used UV-DRS and Fluorescence; for the study of the morphological properties were used HR-TEM and SEM/EDS. The g-C3N4 presented Eg = 2.8 eV, that was displaced to lower energy regions by the metallic nanoparticle deposition. The microscopy images shows the depostion of the nanoparticles and the formation of g-C3N4 nanosheets, indicating the 2D aspect of your structure. The EDS scanning shows the good distribution of the nanoparticles at the surface of the materials.